(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: fosfomycin tromethamine (FT) is an alternative to the treatment of low urinary tract infection (UTI). Uruguay does not have information about its use in children. Objective: to describe the clinical and microbiological evolution of a cohort of children older than 6 years of age with low UTI treated with FT. Materials and methods: we included children of over 6 years of age with low UTI from two health providers in Montevideo between 2/1/2018 and 6/30/2019. We prescribed a single dose of FT 2 g and a control urine culture to all patients. We carried out a telephone follow-up and assessed their clinical record, history of UTI, microorganisms, antimicrobial susceptibility and evolution: time of clinical resolution, microbiological resolution, adverse effects, and recurrence during the first 3 months. Results: 46 children were included, median age 9.4 years, history of UTI 13. 44 presented dysuria, 33 tenesmus, 31 pollakiuria. Isolated microorganism: E. coli 43, S. saprophyticus 2, Proteus sp 1. All susceptible to FT, except S. saprophyticus, naturally resistant. Clinical resolution in 48 hours: 42. Control urine culture was obtained in 31/46 children: microbiological resolution 22, no resolution 5 and contaminated 4. Adverse effects 9: vomiting 1, diarrhea 8, and headache 1. Telephone follow-up carried out for 40 / 46 patients: reinfections after one month of treatment: 6. Conclusions: microorganisms had not acquired resistance. Most cases showed clinical resolution during the first 48 hours. Adverse effects were mild. Reinfections occurred in a small proportion. The results support FT as a therapeutic alternative for low UTI for the case of children of over 6 years of age.